Assessment of animal diseases caused by bacteria resistant to antimicrobials: Horses. (24th December 2021) - ,; Nielsen, Søren Saxmose; Bicout, Dominique Joseph; Calistri, Paolo; Canali, Elisabetta; Drewe, Julian Ashley; Garin‐Bastuji, Bruno; Gonzales Rojas, Jose Luis; Gortazar Schmidt, Christian; Herskin, Mette; Michel, Virginie; Miranda Chueca, Miguel Angel; et al.
Abstract: In this opinion, the antimicrobial‐resistant bacteria responsible for transmissible diseases that constitute a threat to the health of horses have been assessed. The assessment has been performed following a methodology composed of information collected via an extensive literature review and expert judgement. Details on the methodology used for this assessment are explained in a separate opinion. A global state of play of antimicrobial‐resistant Actinobacillus equuli, Dermatophilus congolensis, Enterococcus spp., Escherichia coli, Klebsiella pneumoniae, Pasteurella spp., Pseudomonas aeruginosa, Rhodococcus equi, Staphylococcus aureus and Streptococcus dysgalactiae subsp . dysgalactiae/equisimilis and Streptococcus equi subsp. equi and subsp. zooepidemicus has been provided. Among those bacteria, EFSA identified E. coli, Staphylococcus aureus and R. equi with more than 66% certainty as the most relevant antimicrobial‐resistant bacteria in the EU, given their importance as causative agents of clinical disease in horses and the significant levels of resistance to clinically relevant antimicrobials. The animal health impact of these 'most relevant' bacteria as well as their eligibility of being listed and categorised within the animal health law framework will be assessed in separate scientific opinions.